Role of cytotoxic T-lymphocyte antigen 4 (CTLA-4) expression in the pathogenesis of Warthin’s tumor growth - Alvionika Nadyah Qotrunnada; Tecky Indriana; Jane Kosasih; Meiske Margaretha; Mei Syafriadi (Dental Journal, 2022)
Background: One of the benign salivary gland tumors is Warthin’s tumor, which is a benign tumor consisting of a papillary cystic structure covered by a double epithelial layer cells and lymphoid stroma with germinal center. Several cases have reported the Warthin’s tumor transformation into a malignant tumor such as lymphoma that develops from their stromal. Expression of cytotoxic T-lymphocyte antigen 4 (CTLA-4) as part of the immune checkpoint when highly expressed leads to a more rapid development or progression of tumors. Purpose: To analyze CTLA-4 expression in Warthin’s tumors associated with the pathogenesis of its growth through an escape mechanism from immune checkpoints and analyze based on CTLA expression whether this marker has the potential to be used as immunotherapy by administering anti CTLA-4. Methods: The tissue sections slides of Warthin’s tumor (n=8) were stained with Hematoxylin Eosin and immunostained with Recombinant Anti-CTLA4 antibody [CAL49] (ab237712). The slide with positive CTLA-4 is shown as staining on the cell membrane and/or cytoplasm. Observations were carried out using Optilab. The result is presented as figures. Results: Tumor cells expressed of CTLA-4 show in cytoplasm and/or cell membranes of the epithelial and stromal components of Warthin’s lymphoid. CTLA-4 is expressed lymphoid stroma, which is associated with inhibition of T cell activity against tumor cells, while the exact mechanism of CTLA-4 expression in epithelial components is not known but is thought to induce tumorigenesis and inhibit apoptosis. Conclusion: CTLA-4 is expressed in epithelial and stromal cells of Warthin’s tumor and this expression indicates that Warthin’s tumor cell growth is through the escape mechanism of the CTLA-4 check point immune. Further research is necessary to investigate whether CTLA-4 expression in lymphoid stroma has relate to their transformation toward a malignant tumor of lymphoma.